Elevated Pulse Pressure Levels Are Associated With Increased In-Hospital Mortality in Acute Spontaneous Intracerebral Hemorrhage. (19th April 2017) - Chang, Jason J.; Khorchid, Yasser; Dillard, Kira; Kerro, Ali; Burgess, Lucia Goodwin; Cherkassky, Georgy; Goyal, Nitin; Chapple, Kristina; Alexandrov, Anne W.; Buechner, David; Alexandrov, Andrei V.; Tsivgoulis, Georgios
Abstract: OBJECTIVES: Clinical outcome after intracerebral hemorrhage (ICH) remains poor. Definitive phase-3 trials in ICH have failed to demonstrate improved outcomes with intensive systolic blood pressure (SBP) lowering. We sought to determine whether other BP parameters—diastolic BP (DBP), pulse pressure (PP), and mean arterial pressure (MAP)—showed an association with clinical outcome in ICH. METHODS: We retrospectively analyzed a prospective cohort of 672 patients with spontaneous ICH and documented demographic characteristics, stroke severity, and neuroimaging parameters. Consecutive hourly BP recordings allowed for computation of SBP, DBP, PP, and MAP. Threshold BP values that transitioned patients from survival to death were determined from ROC curves. Using in-hospital mortality as outcome, BP parameters were evaluated with multivariable logistic regression analysis. RESULTS: Patients who died during hospitalization had higher mean PP compared to survivors (68.5 ± 16.4 mm Hg vs. 65.4 ± 12.4 mm Hg; P = 0.032). The following admission variables were associated with significantly higher in-hospital mortality ( P < 0.001): poorer admission clinical condition, intraventricular hemorrhage, and increased admission normalized hematoma volume. ROC analysis showed that mean PP dichotomized at 72.17 mm Hg, provided a transition point that maximized sensitivity and specific for mortality. The association of this increased dichotomized PP with higher in-hospital mortality was maintained in multivariable logistic regression analysis (odds ratio, 3.0; 95% confidence interval, 1.7–5.3; P < 0.001) adjusting for potential confounders. CONCLUSION: Widened PP may be an independent predictor for higher mortality in ICH. This association requires further study.